2023
DOI: 10.3390/ijgi12090349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustainable Development Potential of High-Speed Railway Station Areas Based on “Node-Place-Industry” Model

Zhuojun Zou,
Yiwen Tang

Abstract: The development of the HSR station area is the result of the combined effect of the three elements of transport, place, and industry. This study introduces the industrial dimension and constructs the node-place-industry model to empirically analyze the development potential of station areas along the Hunan section of the Beijing–Guangzhou and the Shanghai–Kunming high-speed railway lines. The results show that (1) the development of the three spatial elements of the station area is mostly out of sync, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The relative importance of index i compared to index j was denoted as α ij . Thus, the expression for the fuzzy judgment matrix M is as described in Equation (2).…”
Section: Ahp Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative importance of index i compared to index j was denoted as α ij . Thus, the expression for the fuzzy judgment matrix M is as described in Equation (2).…”
Section: Ahp Methodsmentioning
confidence: 99%
“…(1) In the semantic feature level, Kansei words such as elegant, introverted, and other words that reflect refined, understated, delicate, and dynamic aesthetics can be used as an aesthetic design guide in the context of sustainable development. (2) In the form features level, the simple and smooth form can better make people perceive the sustainable design aesthetic characteristics.…”
Section: Kansei Image Analysis Of Aesthetic Design Under the Backgrou...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in publications (Kurhan et al, 2023;Kurhan et al, 2022a;Zou and Tang, 2023) have demonstrated that taking into account the population size attracted to HSR and the volume of transit passenger transportation alone is insufficient to achieve the normative investment payback. As mentioned above, this situation can only be rectified by implementing mixed traffic involving high-speed passenger trains and accelerated freight trains (Kurhan et al, 2022b).…”
Section: Southbound Routementioning
confidence: 99%